2023
DOI: 10.3390/ph16040630
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety Profile of Dupilumab in Chronic Rhinosinusitis with Nasal Polyps: Real-Life Data in Tertiary Care

Abstract: Chronic rhinosinusitis with nasal polyps (CRSwNP) is characterized by a type 2 pattern of inflammation resulting in the production of some cytokines. Dupilumab radically changes the treatment of CRSwNP, but, considering its recent approval, it may be useful to evaluate its safety profile in a real-world setting. This work aimed to prospectively highlight the effectiveness and safety profile of dupilumab in patients with CRSwNP enrolled in the Otorhinolaryngology Unit of the University Hospital of Messina. An o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…This mechanism of action determines an arrest of the reparative remodeling events typical of chronic rhinosinusitis with nasal polyps based on type 2 inflammation [ 22 ]. During 2021 EMA and AIFA authorized the use of Dupilumab in type 2 nasal polyposis, therefore, since January 2021, for the first time in Italy, Dupilumab has become part of the therapeutic treatment of nasal polyposis [ 29 ]. SINUS-24 and SINUS-52 studies indeed demonstrated that the administration of Dupilumab (300 mg every 2 weeks) to standard therapy in adults with severe CRSwNP was evaluated in parallel groups and compared to patients riceiving placebo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism of action determines an arrest of the reparative remodeling events typical of chronic rhinosinusitis with nasal polyps based on type 2 inflammation [ 22 ]. During 2021 EMA and AIFA authorized the use of Dupilumab in type 2 nasal polyposis, therefore, since January 2021, for the first time in Italy, Dupilumab has become part of the therapeutic treatment of nasal polyposis [ 29 ]. SINUS-24 and SINUS-52 studies indeed demonstrated that the administration of Dupilumab (300 mg every 2 weeks) to standard therapy in adults with severe CRSwNP was evaluated in parallel groups and compared to patients riceiving placebo.…”
Section: Discussionmentioning
confidence: 99%
“…It also relieved core symptoms of CRSwNP such as nasal congestion or obstruction, nasal discharge and loss of smell, and reduced the use of systemic corticosteroids and the need for surgery, providing effective treatment for patients with severe CRSwNP who would otherwise be left with few treatment options. The drug was generally well tolerated and demonstrated an acceptable level of safety [ 29 ]. Conjunctivitis was reported in seven patients who received dupilumab and one patient who received placebo; none of these patients had serious, severe, or associated symtoms with treatment discontinuation.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 63 patients were included in the study. The Sino-Nasal Outcome Test 22 (SNOT-22) and nasal polyps score (NPS) were shown to present significant reductions at the 6th and 12th months compared to baseline values [67,68]. Table 3 summarizes the characteristics of main studies about the Anti-IL4/IL13 compounds.…”
Section: Anti-il4/il13mentioning
confidence: 99%
“…In the clinical trials safety profiles were similar for patients in the intervention group and placebo group, with a low number of serious adverse events (AEs) (Ortega et al, 2014;Bleecker et al, 2016;Castro et al, 2018). More recently post-marketing studies confirm the low incidence of serious AEs in patients receiving anti-T2 biologicals, while identifying previously unknown risks (Sousa et al, 2020;Bettuzzi et al, 2022;Galletti et al, 2023). Anaphylaxis signals have been described for omalizumab, benralizumab, reslizumab, and mepolizumab (Li et al, 2021).…”
Section: Introductionmentioning
confidence: 90%